Report of Commissioners on Revision of Ordinances 141 (1882) - (:unkn) unknown (My University, 1882)
Whoever sells to a child under the age of sixteen years, without the written consent of its parent or guardian, any cartridge or fixed ammunition of which any fulminate is a component part, or a gun, pistol, or other mechanical contrivance arranged for the explosion of such cartridge or of any fulminate, shall be liable to a penalty of not less than five nor more than fifty dollars.
Keywords: TRANSFER - MINORS